2022
DOI: 10.1038/s41598-021-04012-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant inbred lines and next-generation sequencing enable rapid identification of candidate genes involved in morphological and agronomic traits in foxtail millet

Abstract: We constructed recombinant inbred lines (RILs) between a Japanese and a Taiwanese landrace of foxtail millet and employed next-generation sequencing, such as flexible ddRAD-seq and Nanopore sequencing to identify the candidate genes involved in the crop evolution of foxtail millet. We successfully constructed a linkage map using flexible ddRAD-seq with parents and RILs and detected major QTLs for each of three traits: leaf sheath colors, spikelet-tipped bristles (stb), and days to heading (DTH). (1) For leaf s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…The obtained SNPs were distributed throughout the sorghum genome indicating the effectiveness of this technique, which made it possible to identify a large number of polymorphisms at a low cost ( Peterson et al., 2012 ). The ddRAD-Seq technique has recently been utilized successfully in a variety of plants, including foxtail millet ( Fukunaga et al., 2022 ), Brassica napus ( Chen et al., 2017 ; Scheben et al., 2020 ), and sesame ( Yol et al., 2021 ). To our knowledge, this study is the first to demonstrate that ddRAD-Seq is a suitable approach to detect variants at a genome-wide scale in the sorghum genome.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained SNPs were distributed throughout the sorghum genome indicating the effectiveness of this technique, which made it possible to identify a large number of polymorphisms at a low cost ( Peterson et al., 2012 ). The ddRAD-Seq technique has recently been utilized successfully in a variety of plants, including foxtail millet ( Fukunaga et al., 2022 ), Brassica napus ( Chen et al., 2017 ; Scheben et al., 2020 ), and sesame ( Yol et al., 2021 ). To our knowledge, this study is the first to demonstrate that ddRAD-Seq is a suitable approach to detect variants at a genome-wide scale in the sorghum genome.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 23,000 SNPs were identified from the study across the genomes ( Kumar et al., 2016 ). Next-generation sequencing of recombinant inbred lines (RILs) was performed to identify candidate genes controlling important morphological and agronomical traits in foxtail millet ( Fukunaga et al., 2022 ). In proso millet, the first linkage map and QTLs for agronomic traits were reported by Rajput et al.…”
Section: Discussionmentioning
confidence: 99%
“…The other heading time-associated gene that was thoroughly examined is Pseudo-response regulator 37 ( SiPRR37 ). Recently, two research groups found that this gene plays an important role in the latitudinal adaptation of foxtail millet [ 99 , 100 ]. Li et al [ 99 ] investigated Chinese landraces of foxtail millet using a genome-wide association study (GWAS) and found that transposable element (TE) insertion into SiPRR37 was important for the adaptation of foxtail millet to Northeast China by genotyping 312 accessions (mostly from China), whereas Fukunaga et al [ 100 ] found TE insertion in a Taiwanese landrace by QTL analysis of recombinant inbred lines derived from a hybrid between a Japanese landrace and a Taiwanese landrace.…”
Section: Evolution Of Some Genes ( Waxy ...mentioning
confidence: 99%
“…Recently, two research groups found that this gene plays an important role in the latitudinal adaptation of foxtail millet [ 99 , 100 ]. Li et al [ 99 ] investigated Chinese landraces of foxtail millet using a genome-wide association study (GWAS) and found that transposable element (TE) insertion into SiPRR37 was important for the adaptation of foxtail millet to Northeast China by genotyping 312 accessions (mostly from China), whereas Fukunaga et al [ 100 ] found TE insertion in a Taiwanese landrace by QTL analysis of recombinant inbred lines derived from a hybrid between a Japanese landrace and a Taiwanese landrace. They found that TE insertions are predominantly distributed in Southern Asia, such as the Nansei Islands of Japan, Taiwan, the Philippines, Indonesia, Thailand, Myanmar, Bangladesh, India, Nepal, Pakistan, and Afghanistan, as well as in Kenya, and they sporadically occur in Ukraine and East Asia, including China, Korea, and Japan, according to the genotyping of 99 foxtail millet landraces from Eurasia and Africa ( Figure 5 ).…”
Section: Evolution Of Some Genes ( Waxy ...mentioning
confidence: 99%